2020
DOI: 10.1155/2020/8866187
|View full text |Cite
|
Sign up to set email alerts
|

GPER-Deficient Rats Exhibit Lower Serum Corticosterone Level and Increased Anxiety-Like Behavior

Abstract: Ample evidence suggests that estrogens have strong influences on the occurrence of stress-related mood disorders, but the underlying mechanisms remain poorly understood. Through multiple approaches, we demonstrate that the G protein-coupled estrogen receptor (GPER) is widely distributed along the HPA axis and in brain structures critically involved in mood control. Genetic ablation of GPER in the rat resulted in significantly lower basal serum corticosterone level but enhanced ACTH release in response to acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Furthermore, we found that the distribution of GPER immunofluorescence in various tissues using LS-A4272 was consistent with GPER mRNA expression (Zheng, et al, 2020).…”
Section: Acute Mechanical Itch (Alloknesis)supporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, we found that the distribution of GPER immunofluorescence in various tissues using LS-A4272 was consistent with GPER mRNA expression (Zheng, et al, 2020).…”
Section: Acute Mechanical Itch (Alloknesis)supporting
confidence: 71%
“…This pilot data suggests that GPER signaling may be important in itch regulation. To further investigate the role of GPER signaling in acute and chronic itch, we utilized the GPER-knockout (GPER -/-) rats (Luo, et al, 2017;Zheng et al, 2020) and mice. It is worth mentioning here that during daily handling or the acclimatization period before behavior tests, spontaneous scratches were similarly rare in GPER -/rats and mice as in their WT counterparts (Fig.…”
Section: Gper Deficiency Results In Hypersensitivity To Itch In Mice ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported increased GPER levels in GAD, which further correlated with the anxiety severity in patients irrespective of gender [ 191 ]. In rodents, GPER-deficient rats showed anxiety-like behaviors, as well as low corticosterone [ 192 ]. Interestingly, reports show ERβ signaling has anxiolytic effects [ 193 ], and in mice, ERβ deficiency has been associated with social and mood-related behavioral disturbances via the oxytocin and arginine-vasopressin signaling pathways [ 194 ].…”
Section: Estrogen Receptor and Psychiatric Disordersmentioning
confidence: 99%
“…Our results are in contrast to the study of Trejter et al ( 2015 ) who described that ERα is the highest expressed. It is important to point out that they circumscribed their study to the adrenal cortex, not considering the adrenal medulla, which was demonstrated to be a relevant region of GPER localization (Hazell et al, 2009 ; Zheng et al, 2020 ). The specific role of GPER in adrenal glands is not yet fully understood but it seems that GPER-deficient rats showed a decreased corticosterone basal serum level in both sexes and an increased adrenaline basal serum level in females (Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%